From “Guilty Pleasure” to Critique: Critical Discourse Studies, Reflexivity and Pop Culture - Stamou, Anastasia G. (The Greek Review of Social Research, 2025)
This reflexive article traces my trajectory in Critical Discourse Studies (CDS) and pop culture, exploring the recurring tension between scholarly “guilt” and personal “pleasure.” Growing up, watching Greek popular TV programs was a cherished pastime among the women in my family, yet it often clashed with the cultural values of our leftist background, which prioritized politically engaged art and critical thinking. I argue that CDS faces a similar challenge, frequently privileging the analysis of elite voices while neglecting the affective dimensions of meaning making. Adopting a more reflexive approach could help CDS become more inclusive, theoretically vibrant, and socially relevant.